Could direct transdeltoid approach to severely displaced proximal humerus fracture be advantageous for a better reduction? - Maluta, Tommaso; Amarossi, Andrea; De Masi, Manuel; Dorigotti, Andrea; Ricci, Matteo; Vecchini, Eugenio; Negri, Stefano; Samaila, Elena Manuela; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2022)
Background: Surgical treatment of proximal humeral fractures (PHF) is a challenge for orthopaedic surgeons. Despite the wide application of open reduction and internal fixation with locking plates, the optimal surgical approach of PHF is still debated. This study aims to evaluate the radiological outcomes, defined as anatomical restoration of the greater tuberosity and humeral head-shaft angle, of the deltopectoral (DPA) and the lateral transdeltoid (LTA) approaches in three- and four-part PHF, treated with locking plate. Materials and methods: This retrospective series review identifies 74 PHF surgically treated between January 2012 and December 2019. Patients were divided into two groups according to the surgical approach (DPA vs LTA). Demographic data, duration of surgery, radiological pre- and post-surgery parameters (greater tuberosity displacement and humeral head-shaft angle) were collected. The association between the surgical approach and the quality of fractures reduction was assessed. Results: The use of LTA approach correlates with a better reduction of greater tuberosity displacements compare to DPA (63% in DPA vs 100% LTA). No significant association was found with the humeral head-shaft angle (restored in 89% of the patients in DPA and 86% in LTA group), and surgical times (range 40 – 210 minutes ± DS 33,56 for the DPA; range 45 – 170 minutes ± 29,60 for LTA). Conclusions: The results of this radiological study suggest that PHF with significant displacement of the grater tuberosity could benefit from the adoption of a lateral transdeltoid approach for the ORIF procedure. Further studies are needed to confirm these findings.